T4 Global spread of mycobacterium abscessus clones amongst cystic fibrosis patient. (15th November 2016) - Grogono, DM; Bryant, JM; Rodriguez-Rincon, D; Everall, I; Brown, KP; Moreno, P; Verma, D; Hill, E; Drijkoningen, J; Haworth, CS; Harris, SR; Ordway, D; et al.
Abstract : Introduction: Lung infections with Mycobacterium abscessus, a species of multidrug resistant nontuberculous mycobacteria, have increased in frequency worldwide, emerging as an important global threat to individuals with cystic fibrosis (CF) where they cause accelerated inflammatory lung damage and death. M. abscessus was previously thought to be independently acquired by susceptible individuals from the environment. However, using whole genome sequencing and detailed epidemiological analysis of a cohort of patients attending the CF centre at Papworth Hospital, we found strong evidence for transmission between patients. We therefore sought to examine the mechanism of acquisition of M. abscessus in CF individuals across the world. Methods: We undertook whole genome sequencing on 1080 isolates from 517 patients from the UK, US, the Republic of Ireland, mainland Europe and Australia. This was then correlated with clinical metadata and phenotypic functional analysis. Results: Our genomic analysis revealed that the majority of infections are from densely clustered M. abscessus genotypes with low levels of diversity, indicating a high level of human associated spread. Moreover, the phylogeny reveals the presence of three recently emerged dominant circulating clones that have globally spread. We found that these clones are associated with worse clinical outcomes and show increased virulence in both cell-based and mouse infection models. Within patients we found evidence of genetic diversity and evolutionary adaptation through the processes of convergent evolution and hypermutation. Conclusions: The majority of M. abscessus infections in patients with Cystic Fibrosis are caused by genetically related clusters, indicating recent patient-to-patient transmission despite conventional infection control measures. Transmission appears to have facilitated evolution of M. abscessus from an environmental organism into a transmissible human pathogen. This work was supported by The Wellcome Trust grant 098051 (JMB, SH, JP) and 107032AIA (DG, RAF) The Medical Research Council (JMB), The UK Cystic Fibrosis Trust (DMG, DR-R, IE, JP, RAF), Papworth Hospital (DMG, KPB, CSH, RAF), NIHR Cambridge Biomedical Research Centre (RAF), and The UKCRC Translational Infection Research Initiative (JP).